Використання позитивного досвіду Великобританії у професійній підготовці майбутніх учителів гуманітарних дисциплін в Україні - Катревич, Людмила (Studies in Comparative Education, 2015)
У статті проаналізовано основні проблеми професійної підготовки майбутніх учителів гуманітарного профілю у ВНЗ України. Представлено елементи позитивного досвіду підготовки цих фахівців в університетах Великобританії. Увагу зосереджено зокрема на змістовому та методо-логічному компонентах підготовки. На основі порівняльного аналізу запропоновано рекомендації щодо вдосконалення підготовки педагогів гуманітарного профілю в Україні з використанням позитивного досвіду Великобританії. В статье представлены основные проблемы в профессиональной подготовке будущих учителей гуманитарного профиля в вузах Украины. Представлены элементы положительного опыта подготовки этих специалистов в университетах Великобритании. Внимание сосредоточено в частности на содержательном на методологическом компонентах подготовки. На основе сравнительного анализа предложены рекомендации по совершенствованию подготовки педагогов гуманитарного профиля в Украине, используя положительный опыт Великобритании. In the article, the main disadvantages of professional training of future teachers of humanities in Ukraine’s universities are shown. The elements of positive experience of these specialists’ training in Great Britain’s universities are revealed. The attention is paid mainly to content and methodic components of training. On the basis of contrastive analyses, the recommendations have been suggested for the improvement of professional training of future teachers of humanities in Ukraine using Great Britain’s positive experience. Among the important ideas are the following: to introduce separate specialties on civic education and religious studies for secondary school teachers; to realize transparent professional selection of applicants through professionally-oriented and psychological testing; to include subjects of students’ personal choice in the curricula of humanitarian and pedagogical specialties at all universities and the amount of optional training courses, which should be studied during each semester, must be determined by the Ministry of Education; to give autonomy to universities in developing curricula of optional courses according to the research work of lecturers; to develop the content of training programs inclusing modern international tendencies, problems of multicultural education, European values etc.; to use innovative technologies and methods of training based on the idea of learning through interaction with others, searching for solutions of problem situations, providing students’ free, independent educational activities; to use appropriate forms and methods of knowledge assessment for developing a certain level of communicative skills, critical thinking skills and creative abilities of future teachers of humanities; to apply educational potential of interdisciplinary approach, to combain knowledge of different humanities. The importance and opportuneness of these recommendations for Ukrainian education are emphasized. The article concludes that the ultimate goal of professional development at every level of training is to form a specialist, a teacher who can realize his potential and meet his educational needs, encourage himself to self-development and self-improvement.